A importância da ludicidade no ensino da matemática nos anos iniciais do ensino fundamental - Carvalho, Angélica Holanda de (Universidade Federal Rural do Semi-Árido, 2018)
The playfulness, theme of this research is related to games and games that provide both joy and fun for children. Therefore, this research project aims to analyze and understand how the inclusion of playfulness in math classes in the early years, the Elementary School teacher Maria Barbosa Edilce can positively influence the learning of this discipline. The issue of research considers studies showing that many students do not learn mathematics as they should, considering it a difficult and uninteresting discipline, thus causing a lag in content year after year, negatively impacting the course of the student trajectory of these students, resulting in discouragement and aversion to mathematics. The methodology we used field research and literature, seeking to collect concrete data with theoretical background and analysis of reality in a primary school. As a result, it was proven that the playfulness helps in the teaching-learning process by allowing a better interest and participation of children in activities. Therefore, it is necessary to include the playfulness to make classes more dynamic and attractive to students, encouraging their learning.
Artigo Acadêmico
Keywords: Ludicidade; Matemática; Aprendizagem; Pesquisa; Playfulness; Mathematics; Learning; Research; CIENCIAS EXATAS E DA TERRA::MATEMATICA